PELATIHAN PEMBUATAN PANEL GEOPOLIMER FLY ASH DI DESA SURANADI SEBAGAI PENGGANTI PAPAN KAYU - I Dewa Made Alit Karyawan; Ery Setiawan; Rohani Rohani; Ida Ayu Oka Suwati Sideman; I Gede Putu Warka (Jurnal Abdi Insani, 2023)
The problem found is the high price of raw materials and homestay furniture. It's hard to get quality wood planks at low prices. On the other hand, public knowledge is still limited in finding products as substitute materials at low prices. So construction tends to use materials of poor quality, the important thing is that the price is affordable. So the life of buildings and furniture becomes shorter and is not good from an aesthetic point of view. Based on these problems, a solution is sought that refers to the priorities that have been set, namely the innovation of cheap panel/board products by utilizing waste (fly ash). The method adopted is to provide training to builders on how to make panels from geopolymer fly ash. Thus, the purpose of the community service program carried out by the LPPM Unram Community Service Team is to provide skills to carpenters in making boards/panels from geopolymer fly ash. The method used is to provide training. The training emphasizes the ability to hone participants' skills in choosing materials, mixing materials according to composition, and printing geopolymer paste into panels (boards). The training covers work procedures and stages of technology application. At the end of each activity, an evaluation is carried out so that it can be seen what the achievements and shortcomings are. Activities range from socialization, training preparation, and training implementation to implementation evaluation. As a result, after attending the training, the participants were able to make geopolymer panels (boards) made from fly ash and alkaline. add insight and knowledge and skills. This can be seen from the ability of the training participants (builders and hotel managers) based on the materials and examples provided during the training.